2018
DOI: 10.1016/j.wneu.2018.08.128
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Profile Versus Cage and Plate in Anterior Cervical Discectomy and Fusion with a Minimum 2 Years of Follow-Up: A Meta-Analysis

Abstract: The zero-profile and cage and plate structures achieved comparable mid-term and long-term clinical and radiological outcomes in ACDF. In addition, the zero-profile group showed reduced intraoperative blood loss, improved postoperative C2-C7 Cobb angle, and decreased incidence of dysphagia and adjacent segment degeneration complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
4
33
0
3
Order By: Relevance
“…This design has greater advantages in decreasing incidence of postoperative dysphagia and ASD complications. As demonstrated in several clinical studies, the Zero-P group had a significantly reduced incidence of ASD compared with the PCC group [61][62][63][64][65][66][67]. Our kinematics simulation study showed a lower hypermobility in adjacent segments in the Zero-P fusion model than that in the standard PCC fusion model (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…This design has greater advantages in decreasing incidence of postoperative dysphagia and ASD complications. As demonstrated in several clinical studies, the Zero-P group had a significantly reduced incidence of ASD compared with the PCC group [61][62][63][64][65][66][67]. Our kinematics simulation study showed a lower hypermobility in adjacent segments in the Zero-P fusion model than that in the standard PCC fusion model (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Numerous studies have found no differences in GSP development when comparing the effects of implanted Zero-P ® cage and cage fixed by the conventional cervical plate 3,14,16,17 . Son et al however refer a more significant global lordotisation after the implantation of the anchored cage in comparison to a cage fixed by the conventional plate 18 . CS had no significant impact on the clinical outcome after ACDF 19,20 .…”
Section: Discussionmentioning
confidence: 96%
“…48 Previously published meta-analyses have found a statistically significant increase of dysphagia in patients who underwent ACDF with anterior plate compared with standalone ACDF. 35,49 A large meta-analysis also showed that ACDF with anterior plating has higher rates of developing dysphagia when compared with CDA. 12 In this metaanalysis, which included a total of 527 patients in comparative studies measuring dysphagia, patients undergoing CDA had a lower risk ratio of developing dysphagia when compared with stand-alone ACDF but without statistical significance (P ¼ .2368).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…55,56 When measuring outcomes of stand-alone ACDF compared with traditional ACDF, previous studies have validated the use of stand-alone ACDF techniques when assessing NDI, VAS, and JOA scores and rates of successful fusion. 35,40,49,57 Of note, stand-alone devices were found to be an effective treatment option for patients with up to 3-and 4-level spine disease as well. 57,58 However, one potential disadvantage of the standalone technique is an increased incidence of subsidence in the stand-alone device fusions when compared with traditional ACDF that is described in literature.…”
Section: Summary Of Evidencementioning
confidence: 99%